The identity of the exotic Pterygoplichthys sailfin catfishes in Sri Lanka (Teleostei: Loricariidae) - Abesinghe, Akila; Sudasinghe, Hiranya; Amarasinghe, Anjalie; Fareed, Fazla; Senavirathna, Tharani; Meegaskumbura, Madhava (Zootaxa, 2020)
Invasive alien species (IAS) are a major threat to biodiversity and have contributed to population declines in native species worldwide (Vilà et al. 2011; Gurevitch & Padilla 2004). IUCN’s Invasive Species Specialist Group lists some 80 invasive or potentially invasive species in Sri Lanka, which is part of a global biodiversity hotspot (Myers et al. 2000; Marambe et al. 2011). The major release of aquatic IAS on the island are routed through the ornamental-fish industry (Marambe et al. 2011; Sudasinghe 2016), though a minority represents deliberate, if unplanned, introductions by governmental and non-governmental agencies (Marambe et al. 2011).